Formulation of sub‐micron emulsions containing docosahexaenoic acid esterified in triacylglycerols or phospholipids. Issue 11 (23rd September 2013) - Kabri, Tin‐Hinan; Meynier, Anne; Bontemps, Delphine; Gaillard, Cédric; Foucat, Loic; Linder, Michel; Genot, Claude
<x xml:space="preserve">Abstract</x> In food applications, long‐chain PUFA can be carried by different lipid molecules, which can affect their end‐use properties. The objective of this study was to formulate emulsions containing DHA located exclusively in phospholipids (PL‐DHA) or in triacylglycerols (TAG‐DHA) and with similar fatty acid profiles and organization. Food grade oils and lecithins were blended on the basis of their fatty acid (FA) contents and submitted to high‐pressure homogenization with mineral water. The lecithin containing PL‐DHA allowed to stabilize oil‐in‐water emulsion with droplet average diameter around 240 nm thank to the interfacial molecular packing of the PL species comprising lyso and anionic phospholipids. Small particles around 40 nm were also highlighted by transmission electron microscopy (TEM). To stabilize TAG‐DHA emulsion with mainly soybean phosphatidylcholine, Tween‐80 was selected among other co‐emulsifiers. This TAG‐DHA emulsion presented an average droplet diameter of 203 nm and contained small particles (20 nm) viewed by TEM. It had less negative droplet charge and lower supramolecular diffusion coefficient than PL‐DHA emulsion. It was less physically stable than PL‐DHA emulsion whose droplet size distribution remained unchanged during at least 19 days at 37°C concomitantly with an increase of 1H NMR FA molecular diffusion coefficient. Practical applications: The sub‐micron emulsions designed in this study were physically stable during storage. They were prepared with food‐grade oils and characterized by similar FA compositions and structures. They can be used as delivery systems with FA compositions responding to nutritional recommendations.